ESTIMATION OF RADIATION EXPOSURE ASSOCIATED WITH THE SALINE SOIL OF LAHORE, PAKISTAN - Akhtar, Nasim; Tufail, M.; Chaudhry, M. Ashraf; Iqbal, Mohsin (Journal of Research (Science), 2004)
This investigation reports the amount of radioactivity in the barren soil of Lahore, Pakistan. For this purpose, an area of about 60 hectares of saline soil was selected in Rakh Dera Chal near the city of Lahore in the Punjab province of Pakistan. The technique of gamma ray spectrometry was applied using HPGe (high purity germanium) gamma ray detector and a PC based MCA. Activity concentration levels due to 40K, 137Cs, 226Ra and 232Th were measured in 125 saline soil samples collected at a spacing of about 4 hectares at depth level 0 – 25 cm with a step of 5 cm depth. Results indicated that activity concentration of saline soils the concerned radionuclides was as follows: 40K, 524.84 − 601.62 Bq kg-1, 137Cs, not detected (less than the lower detection limit), 226Ra, 24.73 − 28.17 Bq kg-1, and 232Th, 45.46 − 52.61 Bq kg-1. Before the radiometric measurements, chemical analysis for concentration of Na, Ca and Mg was also carried out along with the measurement of electrical conductivity and pH of the soil samples. The range of values of Na (43-50 meq l-1), Ca+Mg (0.3-0.9 meq l-1), pH (8.1 – 9.21) and values of Ec (16.11-20.5 μs cm-1).